2022
DOI: 10.1152/jn.00308.2022
|View full text |Cite
|
Sign up to set email alerts
|

Differential changes in somatosensory evoked potentials and motor performance: pursuit movement task versus force matching tracking task

Abstract: Force modulation relies on accurate proprioception, and force-matching tasks alter cortico-cerebellar connectivity. Cortico-cerebellar (N24) and cortico-motor pathways are impacted following acquisition of a motor tracing task (MTT), measured using both somatosensory evoked potentials (SEPs) and transcranial magnetic stimulation. This study compared changes in early SEP peak amplitudes and motor performance following a force matching tracking task (FMTT) to an MTT. 30 (18 females) right-handed, participants ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 58 publications
7
12
0
Order By: Relevance
“…Furthermore, when completing their retention test, scores remained similar to their post-acquisition measures, if not ever so slightly improved, as error was approximately ∼18-19% less than that of their baseline measures. Previous research has noted similar improvements in performance in response to learning a motor task dependent on force modulation (Ambalavanar et al, 2022). In the current study, similar results were present when assessing absolute performance scores, although those with ADHD had increased absolute error and variability at each phase when compared to neurotypical controls.…”
Section: Behavioral Datasupporting
confidence: 84%
See 4 more Smart Citations
“…Furthermore, when completing their retention test, scores remained similar to their post-acquisition measures, if not ever so slightly improved, as error was approximately ∼18-19% less than that of their baseline measures. Previous research has noted similar improvements in performance in response to learning a motor task dependent on force modulation (Ambalavanar et al, 2022). In the current study, similar results were present when assessing absolute performance scores, although those with ADHD had increased absolute error and variability at each phase when compared to neurotypical controls.…”
Section: Behavioral Datasupporting
confidence: 84%
“…Interestingly, McCracken et al (2022 found contrasting results in those with ADHD when performing a motor acquisition paradigm utilizing different task demands. When completing a visuomotor task, those with ADHD had an increase in the N18, whereas controls had a decrease (McCracken et al, 2022). It is likely that the different task demands in the current study, which were heavily dependent on force-modulation and proprioception, resulted in the reduced N18 in those with ADHD.…”
Section: N18mentioning
confidence: 71%
See 3 more Smart Citations